2013
DOI: 10.2967/jnumed.112.117218
|View full text |Cite
|
Sign up to set email alerts
|

89Zr-Bevacizumab PET Imaging in Primary Breast Cancer

Abstract: Vascular endothelial growth factor (VEGF)-A is overexpressed in most malignant and premalignant breast lesions. VEGF-A can be visualized noninvasively with PET imaging and using the tracer 89 Zr-labeled bevacizumab. In this clinical feasibility study, we assessed whether VEGF-A in primary breast cancer can be visualized by 89 Zr-bevacizumab PET. Methods: Before surgery, breast cancer patients underwent a PET/CT scan of the breasts and axillary regions 4 d after intravenous administration of 37 MBq of 89 Zr-bev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
103
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 145 publications
(112 citation statements)
references
References 26 publications
(28 reference statements)
2
103
1
1
Order By: Relevance
“…Nagengast et al reported similar results with 18 F-labeled ranibizumab, a Fab-fragment binding to VEGF [76,77], and also found good correlation between 89 Zr-bevacizumab uptake and therapeutic response to anti-angiogenic treatment in vivo in mouse-model with ovarian cancer xenografts [78]. The early experiences in breast cancer are also promising with Zrbevacizumab uptake in 26 breast cancer patients [79].…”
supporting
confidence: 62%
“…Nagengast et al reported similar results with 18 F-labeled ranibizumab, a Fab-fragment binding to VEGF [76,77], and also found good correlation between 89 Zr-bevacizumab uptake and therapeutic response to anti-angiogenic treatment in vivo in mouse-model with ovarian cancer xenografts [78]. The early experiences in breast cancer are also promising with Zrbevacizumab uptake in 26 breast cancer patients [79].…”
supporting
confidence: 62%
“…In a study comparing the risks of radiation-induced cancer from mammography, molecular breast imaging, and positron emitting mammography, the cumulative cancer incidence is 15-30 times higher for positron emission mammography and molecular breast imaging than for mammography (113). The estimated radiation burden of 89Zr-bevacizumab-PET is 19 mSv per tracer injection, on the basis of extrapolation from 111 In-bevacizumab data and a dosimetry study on 89Zr-U36, compared with 5.3 mSv for 18 F-FDG PET (114)(115)(116)(117). Besides bevacizumab, other radiolabeled anti-VEGF antibodies such as I-labeled VG76e (118) and HuMV833 (119) have been reported.…”
Section: Targeting Vascular Endothelial Growth Factor (Vegf)mentioning
confidence: 99%
“…When labeled with 89-zirconium ( 89 Zr), bevacizumab preserves its VEGFbinding properties. 89 Zr-Bevacizumab tumor uptake correlated with VEGF tumor levels [108] andmight be valuable for prediction and evaluation of theeffect of VEGF-targetingtherapeutics.Inthe near future,the development of a PET/MRI integrated system will permit the combination of imaging of molecular targets using PET tracers and study of perfusion using MRI [109].…”
Section: Changes In Tumor Blood Flow and Angiogenesismentioning
confidence: 99%